Effectiveness of control measures to prevent occupational tuberculosis infection in health care workers: a systematic review - Bey-Marrié Schmidt; Mark E. Engel; Leila Abdullahi; Rodney Ehrlich (BMC, 2018)
Abstract Background A number of guideline documents have been published over the past decades on preventing occupational transmission of tuberculosis (TB) infection in health care workers (HCWs). However, direct evidence for the effectiveness of these controls is limited particularly in low-and middle-income (LMIC) countries. Thus, we sought to evaluate whether recommended administrative, environmental and personal protective measures are effective in preventing tuberculin skin test conversion among HCWs, and whether there has been recent research appropriate to LMIC needs. Methods Using inclusion criteria that included tuberculin skin test (TST) conversion as the outcome and longitudinal study design, we searched a number of electronic databases, complemented by hand-searching of reference lists and contacting experts. Reviewers independently selected studies, extracted data and assessed study quality using recommended criteria and overall evidence quality using GRADE criteria. Results Ten before-after studies were found, including two from upper middle income countries. All reported a decline in TST conversion frequency after the intervention. Among five studies that provided rates, the size of the decline varied, ranging from 35 to 100%. Since all were observational studies assessed as having high or unclear risk of bias on at least some criteria, the overall quality of evidence was rated as low using GRADE criteria. Conclusion We found consistent but low quality of evidence for the effectiveness of combined control measures in reducing TB infection transmission in HCWs in both high-income and upper-middle income country settings. However, research is needed in low-income high TB burden, including non-hospital, settings, and on contextual factors determining implementation of recommended control measures. Explicit attention to the reporting of methodological quality is recommended. Trial registration This systematic review was registered with PROSPERO in 2014 and its registration number is CRD42014009087.